The effect of variation of dose, time toward cauli flower (Brassica oleracea var BotrytisL.) On hepatic cytochrome P-450 level rats given theophylline - Sunarsih, Endang Sri; hakim, Lukman; ., Sugiyanto; ., Sumantri (INDONESIAN JOURNAL OF PHARMACY, 2011)
Cytochrome  P-450  as  a  major  component  enzyme  system  in  drug metabolism. Activity  enzyme  of  cytochrome  P-450  was  influenced  by  internal and external factors. Vegetables of Brassicaceae such as cauli flower were often consumed  in  the  long  term,  its   has  inductor  activity  of  oxidation  enzyme systems and conjugation reactions. Theophylline as a bronchodilator drugs have the unknown effects on hepatic microsomal enzyme, such as cytochrome P-450 and   have  not  been  many  studies  that  tried  to  prove  it.  The  purpose  of  this study  was  to  prove  the  effects  of Cauliflower  and  indol  on  level  cytochrome  P-450  enzyme.  90  rats  were  divided  into  3  groups.  Group   I,  were  given Theophylline  20  mg/kg  BW.  In  group  II  30  rats  were  treated  with  indole  1,2; 2,4; 3,6 mg/kg BW, and group III 30 rats were treated with cauliflower extract respectively  doses  100,  200,  300  g/kg  BW.  Each  dose  was  given  on  10  rats, each group were divided 2 sub-groups were treated for 5, 10 days. On the last day  of  treatment  were  given  Theophylline  20  mg/kg  BW.   Cytochrome  P-450 enzyme  levels  were  determined  by  the  method  of  Omura  and  Sato(Snell,  and Mullock,1987). An induction cauliflower and indole did not increased levels of hepatic  cytochrome  P-450.  The  long  treatment  and  the   increased  of administered  dose  did  not  enhanced  the  levels  of  hepatic  cytochrome  P-450 enzyme. cauliflower and indole contained in vegetables when consumed together with theophylline drug, would not affect the metabolism of theophyllineKey words: Cauli flower, cytochrome P-450, theophylline, indole, spectrofotometric.